Methodologies for the application of calcium compounds in agropastoral systems: Effects on crop yields - Borges, Wander Luis Barbosa; Hipólito, Jorge Luiz; Tokuda, Flavio Sueo; Gasparino, Adriano Custódio; de Freitas, Rogério Soares; Andreotti, Marcelo [UNESP] (Wiley, 2021)
Soil acidity (pH <4.4) restricts exploration by the root system and impairs crop yield. To contribute to the development of alternative methodologies for correcting acidity in the surface and subsurface layers of soil, the present study evaluated the effects of seven combinations of application technique (surface, incorporation under soil tillage, or subsurface) and calcium (Ca) compounds (limestone [LS], phosphogypsum [PG], and hydrated lime [HL]) on soybean [Glycine max (L.) Merr.] and maize (Zea mays L.) grain yields and on the absorption of macronutrients and dry matter yield of palisade grass (Urochloa brizantha syn. Brachiaria brizantha ‘Marandu’) in a Typic Hapludalf in an agropastoral system in Brazil. The experimental design was randomized complete blocks with four replications. The results support the following conclusions: (a) applying HL plus PG is a viable alternative to applying LS plus PG for soybean and maize crops, (b) incorporating LS by plowing and harrowing is not a viable alternative to applying LS on the surface, (c) applying HL plus PG on the subsurface is superior to applying HL plus PG on the surface for soybean and palisade grass cultivation, (d) incorporating LS plus PG followed by annually applying LS on the surface improves palisade grass crop yield, (e) annually applying LS plus PG 2 yr before and annually applying LS plus PG increase palisade grass crop yield, and (f) annually applying LS or HL plus PG increases the absorption of Mg and S by palisade grass.